2021
DOI: 10.3390/agronomy11101994
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Greenhouse Evaluation of Melia volkensii Extracts for Potency against African Sweet Potato Weevil, Cylas puncticollis, and Fall Armyworm, Spodoptera frugiperda

Abstract: The African sweet potato weevil, Cylas puncticollis, and fall armyworm, Spodoptera frugiperda, are insect pests of economic importance that have a negative impact on sweet potato and maize production, respectively. In this study, we aimed to evaluate the potential of Melia volkensii extracts to protect sweet potato and maize plants against damage by both insect pests. We evaluated extracts from the bark, leaves, pulp and nuts of Melia volkensii for antifeedant activity against C. puncticollis and S. exigua (us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Interestingly, push-pull technology (PPT) and botanical insecticides are among potential candidates to be deployed with RNAi in an integrated fashion. Currently, many studies have shown that the application of bioformulations of botanical materials ( Jaoko et al, 2021 ) and the emission of chemical compounds by PPT ( Khan et al, 2018 ; Midega et al, 2018; Mutyambai et al, 2019 ) provide promising results against S. frugiperda across diverse agro-ecologies, particularly in the African context. For instance, botanical extracts from Melia volkensii L, Azadirachta indica Juss, Schinnus mol L and Phytolacca dodecandra L. displayed antifeedant activity with larval mortality of more than 90% ( Sisay et al, 2019 ; Jaoko et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, push-pull technology (PPT) and botanical insecticides are among potential candidates to be deployed with RNAi in an integrated fashion. Currently, many studies have shown that the application of bioformulations of botanical materials ( Jaoko et al, 2021 ) and the emission of chemical compounds by PPT ( Khan et al, 2018 ; Midega et al, 2018; Mutyambai et al, 2019 ) provide promising results against S. frugiperda across diverse agro-ecologies, particularly in the African context. For instance, botanical extracts from Melia volkensii L, Azadirachta indica Juss, Schinnus mol L and Phytolacca dodecandra L. displayed antifeedant activity with larval mortality of more than 90% ( Sisay et al, 2019 ; Jaoko et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, many studies have shown that the application of bioformulations of botanical materials ( Jaoko et al, 2021 ) and the emission of chemical compounds by PPT ( Khan et al, 2018 ; Midega et al, 2018; Mutyambai et al, 2019 ) provide promising results against S. frugiperda across diverse agro-ecologies, particularly in the African context. For instance, botanical extracts from Melia volkensii L, Azadirachta indica Juss, Schinnus mol L and Phytolacca dodecandra L. displayed antifeedant activity with larval mortality of more than 90% ( Sisay et al, 2019 ; Jaoko et al, 2021 ). As a versatile option, PPT improves the aboveground and belowground plant environment to enhance the plant while making it less suitable for S. frugiperda ( Khan et al, 2018 ; Sobhy et al, 2022 ) and possesses a convincing trait to act with RNAi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this essential crop is under significant threat from pests like the sweet potato weevil (Cylas puncticollis). Research reveals that these pests cause substantial yield losses, both in the fields and during storage after harvest (Jaoko et al, 2021) [4] . Excessive use of pesticides in response to these issues has raised concerns about the well-being of agricultural workers (Marete et al, 2021) [8] , highlighting the necessity for transitioning to sustainable pest control methods.…”
Section: Introductionmentioning
confidence: 99%
“…They are also used therapeutically to cure pain and aches [5] and antimicrobial activity [4][5][6][7]. Leaf and fruit extracts are used as insect repellants [8,9]. The tree is termite resistant [2,8,10] and produces hard timber, comparable to mahogany [11,12].…”
Section: Introductionmentioning
confidence: 99%